Wearable optoacoustic sensing and imaging systems for quantitative and multiparametric blood analysis - Zheng, Zesheng (Nanyang Technological University, 2022)
The various vital signs carried in the blood communicate important knowledge about the physiological status of the cardiovascular system, addressing the pressing need for a quantitative and multiparametric blood analysis method for routine cardiovascular monitoring. There have been plenty of attempts to measure such physiological vital signs noninvasively but generally exhibit very limited blood analyzing functions, i.e., the efforts to adopt the optical, electrochemical and ultrasonic methods are impeded by inadequate penetration, sensitivity, or specificity. Moreover, current blood analysis methods are typically restricted to bulky instruments and complicated clinical procedures. The novel and emerging optoacoustic imaging technique, as a paradigm-shifting technology, provides an unprecedented solution to overcome the difficulties mentioned above for noninvasive multiparametric cardiovascular study. This PhD thesis comprehensively reviews the fundamental inherent causes of optoacoustic inaccuracy. Compensation schemes and algorithms are developed, and the implementations of wearable devices realizing on-skin assessment of several vital signals are detailed.